Access to education amid internal displacements in Zimbabwe: a systematic review - Chimbunde, Pfuurai; Brown, Byron A. (Frontiers in Education, 2026)
IntroductionThe impact of internal displacement on school children during disasters and conflicts remains a global concern. Despite the seriousness of the challenges posed by internal displacements on education, there is a lack of recent systematic reviews on the lived experiences and realities of displaced school children in Zimbabwe.MethodsGuided by the PRISMA protocols, this scoping review evaluated empirical research from Web of Science, Scopus, and EBSCO databases to explore the challenges faced by displaced school children and the mitigation strategies thereof. After reviewing the original 216 entries based on exclusion and inclusion criteria, 6 research studies were selected for analysis. Notwithstanding the paucity of studies on internal displacement and education, the evaluated publications offer in-depth insights into the existing problems in Zimbabwean schools. The challenges faced by internally displaced school children in Zimbabwe between 2015 and 2025 are examined in these English-language articles.ResultsThe findings, mainly derived from qualitative studies and stakeholders other than school children, emphasize that internal displacements not only lead to a loss of quality education but also intensify vulnerabilities and difficulties associated with living in displacement areas. The review highlights the necessity of conducting both quantitative and qualitative studies, or a combination of both, to explore school children’s lived experiences, their realities, and their suggestions for addressing their specific concerns to ensure continuity of education during displacements.DiscussionBeyond Zimbabwe, the study acts as a potential resource for other countries in similar contexts, recognizing that no nation is immune to internal displacements caused by conflicts, civil wars, economic instability, and climate change.